MiR-654-3p targets SRC to suppress tumor growth in non-small cell lung cancer: MiR-654-3p in non-small cell lung cancer - Pang, Min; Jiang, Yongjie; Huang, Yuyan; Ren, Bi; He, Liping; Jiang, Li (Cellular and Molecular Biology, 2023)
Around the world, cancer-related death is primarily caused by lung cancer all the time. MiR-654-3p plays an outstanding role in the development of cancer, but the mechanism of miR-654-3p in non-small cell lung cancer (NSCLC) is uncertain. For this purpose, a quantitative real-time polymerase chain reaction(qRT-PCR) was carried out to detect the expression of miR-654-3p and SRC mRNA. Western blot was used to estimate the level of SRC protein. The mimics enhanced miR-654-3p, while inhibitors knocked it down. Functional experiments were performed to evaluate the proliferation and migration capacities of cells. Flow cytometry assay was utilized to measure apoptosis rates and cell cycles of cells. TargetScan bioinformatics database was queried to identify the probable target gene for miR-654-3p. Dual-fluorescence assay was implemented to verify whether miR-654-3p targets SRC. Subcutaneous tumorigenesis was used to estimate the function of miR-654-3p in vivo. Results showed that low expression of miR-654-3p was found in NSCLC tissues and cells. Up-regulated miR-654-3p suppressed cell proliferation and migration, promoted apoptosis, and blocked cells in the G1 phase, while down-regulated miR-654-3p created the opposite results. Dual-fluorescence assay confirmed that miR-654-3p was directly bound to SRC. Compared with the control group, the effects of miR-654-3p were neutralized in the group, which was co-transfected with miR-654-3p mimics and SRC over-expression plasmids. In vivo, the tumor volume in the LV-miR-654-3p group was smaller than that in the control group. It was concluded that miR-654-3p acts in an anti-cancer role and suppresses tumor progression via regulating SRC, which lays a theoretical foundation for targeted therapy of NSCLC. MiR-654-3p is expected to be a new miRNA-based therapeutic target.